2014
DOI: 10.1523/jneurosci.2204-14.2014
|View full text |Cite
|
Sign up to set email alerts
|

Parvalbumin and GAD65 Interneuron Inhibition in the Ventral Hippocampus Induces Distinct Behavioral Deficits Relevant to Schizophrenia

Abstract: Hyperactivity within the ventral hippocampus (vHPC) has been linked to both psychosis in humans and behavioral deficits in animal models of schizophrenia. A local decrease in GABA-mediated inhibition, particularly involving parvalbumin (PV)-expressing GABA neurons, has been proposed as a key mechanism underlying this hyperactive state. However, direct evidence is lacking for a causal role of vHPC GABA neurons in behaviors associated with schizophrenia. Here, we probed the behavioral function of two different b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(80 citation statements)
references
References 88 publications
4
74
1
1
Order By: Relevance
“…Swerdlow et al 2008). A number of creative strategies have been used to understand this complex genetic landscape and its overlap with brain circuitry, via assessing the PPI-altering effects of gene knockouts, humanized gene insertions (e.g., Risbrough et al 2014), strain differences in regional gene expression (e.g., Shilling et al 2008), drug-induced changes in regional expression of genes identified in postmortem schizophrenia brain tissue (e.g., Dietz et al 2014), and pharmacogenetic manipulations of neural activity in targeted neuron populations via the use of Designer Receptors Exclusively Activated by Designer Drugs (DREADDs) (e.g., Nguyen et al 2014), among other techniques. These strategies are not without potential pitfalls, including the importance of assessing hearing loss in mutant animals as a potential basis for reduced inhibitory effects of auditory prepulses.…”
Section: The Evolution Of Prepulse Inhibition As a Validated Animal Mmentioning
confidence: 99%
“…Swerdlow et al 2008). A number of creative strategies have been used to understand this complex genetic landscape and its overlap with brain circuitry, via assessing the PPI-altering effects of gene knockouts, humanized gene insertions (e.g., Risbrough et al 2014), strain differences in regional gene expression (e.g., Shilling et al 2008), drug-induced changes in regional expression of genes identified in postmortem schizophrenia brain tissue (e.g., Dietz et al 2014), and pharmacogenetic manipulations of neural activity in targeted neuron populations via the use of Designer Receptors Exclusively Activated by Designer Drugs (DREADDs) (e.g., Nguyen et al 2014), among other techniques. These strategies are not without potential pitfalls, including the importance of assessing hearing loss in mutant animals as a potential basis for reduced inhibitory effects of auditory prepulses.…”
Section: The Evolution Of Prepulse Inhibition As a Validated Animal Mmentioning
confidence: 99%
“…It could be the target animal's movement, odor, or sound, or some combination of these factors. A previous study has shown that olfactory cues are sufficient to elicit social approach behaviors in mice (Ryan et al, 2008). However, it is possible that other sensory cues, or their combinations with olfactory cues, contribute to social approach behaviors.…”
Section: Introductionmentioning
confidence: 96%
“…Mouse models of social dysfunction are widely used to investigate neural mechanisms underlying various neuropsychiatric diseases, such as autism spectrum disorders (ASDs), depression, and schizophrenia (Bey and Jiang, 2001;Yang et al, 2011;Ting et al, 2012;Kleijer et al, 2014;Lombardi et al, 2015;Kazdoba et al, 2016). Previous studies have found that the medial prefrontal cortex (mPFC) plays a crucial role in mouse social behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that: (i) KYNA is a known GPR35 agonist [2], (ii) cognitive impairments in patients with schizophrenia and in preclinical rodent models of the disease appear to be linked to decreased interneuron function [34,35], and (iii) GPR35 activation, as shown here, leads to a reduction of SRI firing, it is tempting to hypothesize that KYNA-induced activation of GPR35 in SRIs may be one of the molecular mechanisms underlying the pathophysiology of this catastrophic disorder. If this hypothesis holds true, then centrally acting GPR35 antagonists would emerge as promising therapeutic measures to mitigate signs and symptoms resulting from KYNA-induced disruption of the functionality of hippocampal networks in schizophrenia.…”
Section: Discussionmentioning
confidence: 81%